Mycorrhizal Seed Coating Enhances Root Volume and Yield Components of Edamame Soybean - Indri Fariroh; Didik Pudji Restanto (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2026)
Elevated osmotic pressure in the root zone under saline conditions acts as primary constraint to crop production by disrupting essential physiological growth process. One effective strategy for soil saline management involves the use of mycorrhizal inoculants. Delivering these microbes via seed coating is a streamlined, economical, and accurate approach that optimizes plant performance under diverse stress condition. This study aimed to evaluate the effect of mycorrhizal seed coating on the growth and yield of edamame under saline conditions. This research was arranged in a randomized complete block design with two factors, consisting of mycorrhizal seed coating (0 and 12 g mg-1) and planting media (soil, saline soil, soil + saline soil (1:1)). There were six treatment combinations, and each treatment was replicated four times, resulting in a total of 24 experimental units. The observed variables include plant height, root volume, number of pods per plant, weight of pod per fruit, number of seeds per plant, and weight of 100 seeds. The result showed that mycorrhizal seed coating had potential to improve edamame root development and optimize phosphorus uptake. While vegetative height remained unaffected, the treatment substantially improved yield components, including number of pods, seed weight, and overall seed weight. The efficacy of colonization is contingent upon soil pH and phosphorus availability, highlighting the importance of site-specific conditions. Consequently, mycorrhizal seed coating represents a practical and cost-effective strategy for improving edamame performance, offering a viable solution for enhancing crop resilience and yield in nutrient-deficient or saline environments.